2006
DOI: 10.1080/01690960500139355
|View full text |Cite
|
Sign up to set email alerts
|

From phonological recoding to lexical reading: A longitudinal study on reading development in Italian

Abstract: In this longitudinal study we analyse the early phases of reading development in Italian and explore the transition from phonological to lexical reading. A group of 28 Italian children was tested in four phases. Language and cognitive skills were first assessed in the preschool. Reading performance was then tested in three different sessions, in grade 1 and 2, using off-line naming tasks. To identify lexical reading we included in our test Italian words that have atypical stress assignment and can be pronounce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
48
0
16

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(75 citation statements)
references
References 34 publications
11
48
0
16
Order By: Relevance
“…Los niños de tercero y cuarto grado leen más palabras de ambos grupos de estí-mulos por la vía lexical, disminuyendo así el efecto de la frecuencia que, de todos modos, es aún significativo. Esta interpretación está en línea con los resultados de estudios longitudinales de niños italianos (De Luca, Zeri, Spinelli & Zoccolotti, 2010;Orsolini, Fanari, Tosi, De Nigris & Carrieri, 2006) que muestran la progresión desde una lectura del tipo sublexical hacia una lectura lé -xica, a medida que avanza la escolari zación.…”
Section: Discussionunclassified
“…Los niños de tercero y cuarto grado leen más palabras de ambos grupos de estí-mulos por la vía lexical, disminuyendo así el efecto de la frecuencia que, de todos modos, es aún significativo. Esta interpretación está en línea con los resultados de estudios longitudinales de niños italianos (De Luca, Zeri, Spinelli & Zoccolotti, 2010;Orsolini, Fanari, Tosi, De Nigris & Carrieri, 2006) que muestran la progresión desde una lectura del tipo sublexical hacia una lectura lé -xica, a medida que avanza la escolari zación.…”
Section: Discussionunclassified
“…In transparent orthographies, reading accuracy reaches a ceiling effect after a few months of formal reading instruction (Cossu, Gugliotta, & Marshall, 1995). In fact, Orsolini, Fanari, Tosi, De Nigris and Carrieri (2006) found that Italian first graders are able to read most short words within the first 4 months of schooling while Cossu (1999) found high performance for reading short and long words and pseudo-words by the end of the first semester of school. Tressoldi (1996) also confirmed low error rates in word reading even at second-grade level, while Seymour et al (2003) found that Italian first graders reach 95 % reading accuracy by the end of the school year.…”
Section: Reading-spelling Relationship In Transparent Writing Systemsmentioning
confidence: 96%
“…Phonological awareness influences reading acquisition, and reading acquisition retroactively influences first graders' phonological awareness (McGuinness, McGuinness, & Donohue, 1995). In a transparent writing system, almost all children become generally proficient in phonological awareness at the end of first grade (Orsolini et al, 2006;Ziegler et al, 2010), which improves the child's reading accuracy, and might explain why phonological awareness in first grade does not predict reading disorders (Bigozzi, Tarchi, Pinto, & Accorti Gamannossi, in press). Since children achieve high level of accuracy in reading in transparent writing systems, this criterion cannot be used in reading performance assessments.…”
Section: Reading-spelling Relationship In Transparent Writing Systemsmentioning
confidence: 97%
See 1 more Smart Citation
“…That is, accuracy levels for word reading reach ceiling by third grade, with reading speed improving more slowly since then (Tressoldi et al, 2001). Further evidence relies on the fact that reading fluency of (low-frequency) words after third grade show a significant increase with respect to non-words reading (Orsolini et al, 2006). Additional data indicate that in Italian first and second graders, reading skills appear to be predicted to a great extent only by phonological awareness and RAN, while from third grade on reading competence is no longer influenced by phonological skills, but by vocabulary, RAN, verbal memory (digit span), and visuospatial attention (Tobia and Marzocchi, 2014).…”
Section: Participantsmentioning
confidence: 99%